Radiopharmaceutical administration practices—Are they best practice? - Harris, Stephen; Crowley, James R.; Warden, Nancy (Frontiers in Nuclear Medicine, 2023)
Background The nuclear medicine community has stated that they are using best practices to gain venous access and administer radiopharmaceuticals, and therefore do not contribute to extravasations. We tested this hypothesis qualitatively and quantitatively by evaluating four different perspectives of current radiopharmaceutical administration practices: (1) clinical observations of nuclear medicine technologists on the job, (2) quality improvement (QI) projects, (3) a high-level survey of current practices in 10 acute care hospitals, (4) IV access site data for 29,343 procedures. These four areas were compared to the gold standard of pharmaceutical administration techniques. Results From clinical observations of radiopharmaceutical administrations in adult populations, technologists extensively used 24-gauge (Ga.) peripheral intravenous catheters (PIVCs) and butterfly needles. They also performed direct puncture (straight stick). Technologists predominantly chose veins in areas of flexion (hand, wrist, and antecubital fossa), rather than forearm vessels for intravenous (IV) access placement; in many circumstances, antecubital fossa (ACF) vessels are chosen first, often without prior assessment for other suitable vessels. For selecting the injection vein, technologists sometimes used infrared vein finders but primarily performed blind sticks. Review of QI projects suggested that smaller gauge needles were contributing factors to extravasations. Additionally, the review of surveys from 10 hospitals revealed an absence of formalized protocols, training, knowledge, and skills necessary to ensure the safety/patency of IV devices prior to the administration of radiopharmaceuticals. Finally, findings from a review of IV access data for 29,343 procedures supported the observations described above. Conclusions We expect that nuclear medicine technologists have the best intentions when providing patient care, but many do not follow venous access best practices; they lack formal protocols, have not received the latest comprehensive training, and do not use the best placement tools and monitoring equipment. Thus, the presumption that most nuclear medicine technologists use best practices may not be accurate. In order to improve radiopharmaceutical administration and patient care, the nuclear medicine community should update technical standards to address the most recent peripheral IV access and administration best practices, provide technologists with vascular visualization tools and the proper training, develop and require annual vascular access competency